PEMBUDAYAAN PENDIDIKAN INDONESIA (Sebuah Tuntutan Perubahan Peradaban Bangsa) - Yulius Rustam Effendi (Jurnal Alternatif Wacana Ilmiah Interkultural, 2014)
Themost voluptuous BREAKTHROUGH at century21 happened notonly because of the technology, but also because of the growth of the concept about what is the meaning of becoming a human being.The Existence of human being deals always with a rich “ posibility" and “ actuality". Human being who is always in the process of “ becoming” can only happen through a steady process of education The demand of an urgent process ofeducation aiming at universal human building through certain evolution emerges all the time.Human being is neverconsidered not onlyas "being" but alsoas “becoming, a motion, a process, and transistion, which really never ends. Essentially education deals with human attainment ofhuman being.. Education in this case assist the paradigm shift and facilitate the process of being in solidarity eventhough there is a lot of limitations ( Naisbitt & Aburdene, 1990: 10).In the light of this point of view education cannot be comprehended except as cultural endeavour for the shake of a civil society..Hence the permanent and real solution for the complexity of the problems of our nation is how to invest properlyand correctly the human resources more than any other superficial wayout.